New educational environments aimed at developing intercultural understanding while reinforcing the use of english in experience-based learning (2012)
New learning environments with communication and information tools are increasingly accessible with technology playing a crucial role in expanding and reconceptualizing student learning experiences. This paper reviews the outcome of an innovative course offered by four universities in three countries: Canada, the United States, and Mexico. Course objectives focused on broadening the understandingof indigenous and non-indigenous peoples primarily in relation to identity as it encouraged students to reflect on their own identity while improving their English skills in an interactive and experiential manner and thus enhancing their intercultural competence.Cada vez es más fácil tener acceso a nuevos entornos de aprendizaje que utilizan herramientas de comunicación e información en las que la tecnología desempeña un papel crucial en la expansión y la reconceptualización de las experiencias de aprendizaje del estudiante. En este artículo se revisa el resultado de un curso innovador que se ofreció en cuatro universidades de tres países: Canadá, Estados Unidos y México. Los objetivos del curso se centraron en ampliar la comprensión de los pueblos indígenas y no indígenas, en particular en relación con la identidad. Esto alentó a los estudiantes a reflexionar sobre su propia identidad, a la vez que mejoraban sus habilidades del inglés de una manera interactiva y experimental, logrando así mejorar su competencia intercultural.